Trends and Directions in Online Learning Research in Physics and Astronomy Education: A Bibliometric Analysis - Ishmah Luthfiyah (Universal Education Jurnal Teaching and Learning, 2025)
This study aims to explore the trends and directions in online learning research within the fields of physics and astronomy, with a specific focus on how these disciplines have integrated online learning technologies. Given the rapid advancement in information and communication technologies (ICT), online learning has significantly reshaped education by overcoming traditional constraints of time and geography. This research addresses key questions about the evolution of online learning in these complex subjects, investigating the impact of various educational tools such as simulations, augmented reality (AR), and virtual reality (VR), and identifying the challenges associated with access to technology and digital literacy. To analyze the trends in this field, a bibliometric approach was employed. Data was obtained from the Scopus database, focusing on articles related to "online learning" in physics and astronomy published between 2005 and April 2025. The analysis used tools such as R and VOSviewer to assess publication trends, citation patterns, key authors, and institutional contributions. A total of 472 articles were selected for the analysis, revealing a substantial growth in publications post-2015, particularly after the global pandemic, which spurred interest in online education methods. The findings highlight that the number of publications and citations has increased significantly, with China leading in contributions. Notable sources include journals such as Applied Sciences and Sensors, while key authors like Wang Y and Liu Y have made considerable impacts in this field. Emerging topics in the research include the application of machine learning and the growing integration of personalized learning technologies. These results provide valuable insights into the ongoing development of online learning strategies in physics and astronomy education, emphasizing the need for continued innovation and collaboration in this rapidly evolving area.